Single-cell atlas of the mouse ovary reveals molecular drivers of aging and senescence during the estropausal transition - Xifan Wang; Jiping Yang; Chen Jin; Xizhe Wang; Daniela Contreras; Melody Devos; Maggie M. Kane; Michael G. Rosenfeld; Yousin Suh (Proceedings of the National Academy of Sciences, 2026)
Reproductive aging in mice leads to estropause, characterized by estrous cycle irregularity and eventual cessation, yet its underlying mechanism remains unclear. Here, we present a comprehensive single-cell atlas of mouse ovaries across precisely defined reproductive stages—from young (regular cycling) through the estropausal transition (regular vs. irregular cycling) to post-estropause (acyclic)—and of ovary-specific senescent cells defined by high senescence-associated β-galactosidase activity. We mapped transcriptomic dynamics of ovarian aging and characterized the molecular features of ovarian senescent cells. Our analyses revealed that during the estropausal transition, irregularly cycling ovaries exhibited accelerated aging and cellular senescence features compared with regularly cycling counterparts, including increased transcriptional noise, altered conserved aging pathways such as oxidative phosphorylation and proteostasis, hormone dysregulation in granulosa cells, and elevated expression of the senescence marker Cdkn1a and senescence-associated secretory phenotype factors. This atlas delineates the cellular and molecular hallmarks of mouse ovarian aging and ovary-specific senescent cells, providing a resource for understanding the mechanisms underlying the estropausal transition.